2008
DOI: 10.1021/jp711880e
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature-Stable Au@SnO2 Core/Shell Supported Catalyst for CO Oxidation

Abstract: High-temperature-stable Au@SnO 2 core/shell supported catalyst was prepared by a simple intermetallicsbased dry-oxidation approach in which the size of the core can be controlled easily by varying the size of the pre-made Au seeds. The change of their structure was investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). In the as-prepared supported catalysts, Au particles with a mean size of ca. 15 nm were highly encapsulated by the SnO 2 she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
179
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(188 citation statements)
references
References 27 publications
7
179
1
1
Order By: Relevance
“…SnO 2 was chosen as a protective shell by Yu et al [42] Au particles were prepared to be used as seeds for the subsequent reduction of SnCl 2 to form intermetallic AuSn nanoparticles. By heat treatment, Sn was selectively oxidized to form Au@SnO 2 materials.…”
Section: Goldmentioning
confidence: 99%
“…SnO 2 was chosen as a protective shell by Yu et al [42] Au particles were prepared to be used as seeds for the subsequent reduction of SnCl 2 to form intermetallic AuSn nanoparticles. By heat treatment, Sn was selectively oxidized to form Au@SnO 2 materials.…”
Section: Goldmentioning
confidence: 99%
“…However, the CO conversion was very low when the reaction temperature was below 100 °C . Xie and coworkers synthesized Au@SnO 2 core-shell structures by an intermetallics-based dry-oxidation approach [46]. Gold nanoparticles with a mean size of 15 nm were encapsulated by a SnO 2 shell having a thickness of 6-7 nm.…”
Section: Dispersion Of Au@oxide Core-shell Structures On a Supportmentioning
confidence: 99%
“…Gold nanoparticles with a mean size of 15 nm were encapsulated by a SnO 2 shell having a thickness of 6-7 nm. The core-shell structured catalyst still showed 50% CO conversion when the reaction temperature was 230 °C , even though the catalyst was pretreated at 850 °C prior to reaction [46]. Xu and co-workers synthesized bimetallic Au-Ni nanoparticles embedded in SiO 2 spheres, and demonstrated that the resulting Au-Ni@SiO 2 showed higher catalytic activity and better durability than monometallic Au@SiO 2 or Ni@SiO 2 in the hydrolysis of ammoniaborane [56].…”
Section: Dispersion Of Au@oxide Core-shell Structures On a Supportmentioning
confidence: 99%
“…Due to the strong quantum confinement effect, the band gap energy of PbS nanomaterils can be tuned in the near infrared and even in the visible regions leading them to be employed in a lot of applications such as IR detectors, glucose sensor [2,3], phototransitors [4], solar absorber [5] or materials for luminescent display device [6], recently. Furthermore, metal-semiconductor heterostructures such as Au-PbS, Au-Cu 2 O, Ag-Cu 2 O and AuSnO 2 core-shell nanoparticles or TiO 2 -Ag and ZnO-Au composites have been finding themselves in many applications since they can integrate several functionalities required in one single structure [7][8][9][10][11][12].…”
mentioning
confidence: 99%